Design And Development Of Collision Avoidance Strategy For Differential Drive Mobile Robot - Ng, Sing Yee (Universiti Sains Malaysia, 2018)
Autonomous mobile robots have been considered for many service applications such as intelligent household cleaners and unmanned delivery systems. However, for some specific tasks, a mobile robot must be able to avoid obstacles and move efficiently from a starting point to a goal point. In such a case, a good collision avoidance technique is required where the distance between the robot and the obstacle must be kept non-zero. In this project, a collision avoidance strategy is designed and developed for a differential drive mobile robot, which is built using ATmega 328p microcontroller. Two algorithms, namely Artificial Potential Filed (APF) and Bug 2 are integrated into the model with an ultrasonic sensor to detect and avoid the obstacles. For path planning strategy, the dead-reckoning method is developed to calculate the speed and position control of the robot while discrete proportional-integral (PI) controllers are used to regulate the velocities of both wheels. In order to evaluate the performance of the proposed methods, a MATLAB Graphical User Interface (GUI) is created to plot the targeted and real path of the robot. In this work, it is shown that both algorithms provide good collision avoidance strategy with a maximum error of only 5cm.